PERAN DUTA WISATA MAS DAN MBAK KLATEN DALAM MEMAJUKAN PARIWISATA DI KABUPATEN KLATEN - , RIZA ASSHAFA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Involvement tourism ambassador of Klaten in tourism promotion begins with the selection then elected winner tourism ambassador of Klaten has a service contract with the government and tourism and culture department of Klaten. This final project aims to: 1) Explain the role and duties of a tourism ambassador of Klaten